PERBEDAAN SPESIFIC VALUES ANTARA MAHASISWA AKUNTANSI DAN MAHASISWA KEDOTERAN STUDI EMPIRIS PADA UGM - Siti Fathonah (UGM, 2004)
this study aims to analyze, to compare and to differentiate specific values of accounting and medical students. While the majority of previous studies used the rokeach intrument survey, the current study employs the modified rokeach and schartz instrument. This modified instrument consists of thirty constructs: individuality, theoretical, social, and esthetical. Overall, the study shows that personal values of accounting students are below those of medical students. Based on the finding, the study suggests that a certain subject or course with a high contents should be taught in accounting programs.